Channels of Transmission of Environmental Policy to Economic Growth: A Survey of the Theory - Francesco Ricci (Fondazione Eni Enrico Mattei (FEEM), 2004)
Economists generally hold that environmental regulations impose constraints on the production possibilities set and are therefore potentially harmful to economic growth. In recent years, however, it has been recognized that environmental regulation can enhance the prospects for growth if improved environmental quality increases the productivity of inputs or the efficiency of the education system. It is also held that environmental regulation promotes pollution abatement activity and can lead to the exploitation of increasing returns to scale in abatement. Furthermore, expectations of a better environment may encourage households to save. Finally, it has been conjectured that environmental regulations can stimulate innovation because R&D s a relatively clean activity and because the market share of clean innovations increases.
Keywords: Q28; O41; O13; H23; 330; Environmental policy; Endogenous growth; Umweltpolitik; Wirtschaftswachstum; Endogenes Wachstumsmodell